Fabrication of poly(vinyl alcohol)-graphene quantum dots coated with poly(3, 4-ethylenedioxythiophene) for supercapacitor - Syed Zainol Abidin, Shariffah Nur Jannah; Mamat, Shuhazlly; Abdul Rashid, Suraya; Zainal, Zulkarnain; Sulaiman, Yusran (John Wiley and Sons, 2018)
Conducting nanofiber composed of poly(vinyl alcohol) (PVA), graphene quantum dots (GQDs) and poly(3,4‐ethylenedioxythiophene) (PEDOT) was prepared for symmetrical supercapacitor through electrospinning and electropolymerization techniques. The formation of PVA nanofibers with the addition of GQDs was excellently prepared with the average diameter of 55.66 ± 27 nm. Field emission scanning electron microscopy images revealed that cauliflower‐like structure of PEDOT was successfully coated on PVA‐GQD electrospun nanofibers. PVA‐GQD/PEDOT nanocomposite exhibited the highest specific capacitance of 291.86 F/g compared with PVA/PEDOT (220.73 F/g) and PEDOT (161.48 F/g). PVA‐GQD/PEDOT also demonstrated a high specific energy and specific power of 16.95 and 984.48 W/kg, respectively, at 2.0 A/g current density. PVA‐GQD/PEDOT exhibited the lowest resistance of charge transfer (Rct) and equivalent series resistance compared with PEDOT and PVA/PEDOT, indicating that the fast ion diffusion between the electrode and electrolyte interface. PVA‐GQD/PEDOT nanocomposite also showed an excellent stability with retention of 98% after 1000 cycles.